HUBUNGAN ANTARA ASI EKSKLUSIF DENGAN STUNTING DI WILAYAH KERJA PUSKESMAS BOJONG GENTENG SUKABUMI JAWA BARAT 2023 - Hendi Fulvian Fauzan Nur (2023)
Stunting or short stature is a condition when height or body length for age is more than two standard deviations below the median growth curve. The national stunting rate shows a decreasing trend from 27.7% in 2019 to 24.4% in 2021. Even so, efforts need to be made to reduce it by 2.75% per year to achieve the target of 14% according to the RPJMN (Medium Term Development Plan). ). National, 2020). The stunting rate in West Java Province is 24.5%. The highest prevalence in Sukabumi district is in the working area of the Bojong Genteng Community Health Center at 15.72%. The purpose of this study was to find out the factors that influence exclusive breastfeeding on the incidence of stunting in the working area of the Bojong Genteng Community Health Center, Sukabumi Regency. This research is an analytic observational study using a case-control approach. The results of the logistic regression test showed that the most influential risk factors of all the variables studied were breastfeeding and PMT and adequacy of MP-ASI caloric intake with OR = 0.148 CI = (0.304-0.636) meaning infants with a history of breastfeeding and PMT and adequate intake MP ASI calories have a lower risk of 0.148 times the risk of experiencing stunting